Evaluation And Management Of Twenty Penetrating Ureteric Injuries In Resource-Limited Settings (Journal of Pharmaceutical Negative Results, 2023)
Objective: to evaluate and discuss the treatment of patients who have sustained penetrating ureteral injuries due to causes other than medical care provider error. ‎Methods: All cases of ureteral injury secondary to penetrating trauma was examined a total of 21 ureteral ‎injuries were studied retrospectively which came from 20 patients (one case is bilateral injury and considered as two injuries) . Results: Only two of the twenty patients included in this report were female. Seventy-five percent of the injuries were caused by gunfire, while the remaining twenty-five percent were the result of shell explosions. Only 10% of patients with ureteric injury were properly diagnosed. Roughly one in ten patients undergo a nephrectomy, while one in four undergo a uretero-neocystostomy. .Conclusion: Urinary tract trauma is uncommon, hard to diagnose, and challenging to treat surgically. Many trauma surgeons and urologists lack experience treating these injuries because they are so uncommon. Ureteral injury can cause the loss of an ipsilateral renal unit or significant and delayed complications if it is not diagnosed or treated properly. ‎